Active Child, Accomplished Youth: Middle Childhood Active Leisure Fuels Academic Success by Emerging Adulthood - Laurie-Anne Kosak; Kianoush Harandian; Simon L. Bacon; Caroline Fitzpatrick; Luca Correale; Linda S. Pagani (MDPI AG, 2024)
Background/Objectives: Physical activity is an important protective factor throughout life. However, little research has observed the associations between the practice of physical activity and academic success longitudinally, and none have done so with a pan-Canadian sample. This article aims to examine the prospective associations between active leisure in middle childhood and academic achievement in emerging adulthood, for both boys and girls, beyond several family factors. Methods: Participants are 2775 children from the National Longitudinal Study on Children and Youth (NLSCY) aged between 12 and 20 years. Active leisure was self-reported by children at age 12 years regarding their weekly organized sport, artistic sport, and unstructured physical activity participation outside of school hours. Academic success was measured by self-reported school average at age 18 years and the obtention of high school diploma at age 20 years. Results: Girls who engaged in more organized or artistic sports at age 12 years had better academic results at age 18 years (respectively β = −0.082, p < 0.01; β = −0.228, p < 0.001). Both boys and girls who partook in more organized sports at age 12 years were more likely to graduate from high school by age 20 years (respectively β = −0.146, p < 0.001; β = −0.071, p < 0.05). However, girls who engaged in more unstructured physical activity at age 12 years had lower academic achievement at age 18 years (β = 0.077, p < 0.001). Conclusions: Policy makers should aim to reduce the many barriers to an active lifestyle in childhood. Parents should be encouraged to lead their children to go play outside with friends to allow them to fully reap the benefits of an active lifestyle from a young age.